The Effect of TikTok Shop Utilization Towards the Sales and Profitability of Business Managed by Student Entrepreneurs - Busante, Annjaneth V., Camacho, Atasha Rain F., Chozas, John Emil M., De Castro, Cleo Andrea Mae C., Gervacio, Jesiree E., Paulate, Jared B., Santos, Dread Asshley G., Sarmiento, Angelo Louis A., Sunga, Patrick C. 4 0 16; 5 (2024)
Abstract The present quantitative study investigated the effect of TikTok Shop utilization on the sales and profitability of businesses managed by student entrepreneurs aged 18-24 in the First District of Manila City for the school year 2023-2024. By examining the duration, frequency, knowledge level, and selling experience on TikTok Shop, the study aimed to provide insights into how these factors influenced business performance. Purposive sampling was employed to select participants actively engaged in managing their online shops on the TikTok platform. Data were collected through online surveys distributed via Google Forms, focusing on demographics, TikTok Shop utilization, sales performance, and satisfaction levels. Correlation analyses were conducted to explore the relationships between Tik Tok Shop usage and business performance. The study revealed significant positive correlations between TikTok Shop utilization and both sales and profitability performance among student entrepreneurs. Longer and more frequent usage, coupled with higher knowledge levels and selling experience, correlated with increased sales and profitability. The integration of TikTok Shop led to notable improvements in sales across different volume brackets and overall business profitability. The findings contributed to theories in entrepreneurship, e-commerce, and digital marketing by validating the importance of online platforms in shaping business strategies and outcomes. They emphasized the significance of factors such as technology acceptance and usage behavior in driving the effectiveness of digital platforms among entrepreneurs. This study offered valuable insights into the role of TikTok Shop in enhancing sales and profitability for student entrepreneurs, highlighting its potential to create entrepreneurship among young individuals. The findings had practical implications for digital marketers and e-commerce practitioners, emphasizing the importance of incorporating social media platforms into marketing strategies for business growth. Keywords: TikTok Shop, student entrepreneurs, business performance, sales, profitability, e-commerce, digital marketing, social media platforms.
Business Research: (BSBA major in Financial Management) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2